2021
DOI: 10.3389/fimmu.2021.768397
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vaccination Against Periodontal Disease: Current Status and Opportunities

Abstract: Approximately 9 out of 10 adults have some form of periodontal disease, an infection-induced inflammatory disease of the tooth-supporting tissues. The initial form, gingivitis, often remains asymptomatic, but this can evolve into periodontitis, which is typically associated with halitosis, oral pain or discomfort, and tooth loss. Furthermore, periodontitis may contribute to systemic disorders like cardiovascular disease and type 2 diabetes mellitus. Control options remain nonspecific, time-consuming, and costl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 188 publications
(356 reference statements)
0
14
0
Order By: Relevance
“…7 Therefore, clinicians only have to select conventional therapeutic strategies that involve three main steps: (1) glycemic control, (2) regular periodontal non-surgical treatment, and (3) antibiotic administration. 8,9 Although it has demonstrated a certain extent of efficacy in alleviating diabetic periodontitis (DP), 10 a plethora of related clinical trials have revealed no significant differences in the serum levels of key critical pro-inflammatory cytokines such as TNF-α and IL-6 before and after therapy. 11–13 In addition, related research studies have also claimed that this strategy played a limited role in alleviating the IR level of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Therefore, clinicians only have to select conventional therapeutic strategies that involve three main steps: (1) glycemic control, (2) regular periodontal non-surgical treatment, and (3) antibiotic administration. 8,9 Although it has demonstrated a certain extent of efficacy in alleviating diabetic periodontitis (DP), 10 a plethora of related clinical trials have revealed no significant differences in the serum levels of key critical pro-inflammatory cytokines such as TNF-α and IL-6 before and after therapy. 11–13 In addition, related research studies have also claimed that this strategy played a limited role in alleviating the IR level of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…8,14 What's worse, antibiotic use is not routinely recommended due to the increased bacterial drug resistance which is detrimental to the human body. 9,15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these species, Treponema denticola , Aggregatibacter actinomycetemcomitans , P. gingiyalis , Tannerella forsythia , Campylobacter rectus and Fusobacterium nucleatum are associated with periodontitis [ 19 ]. No vaccine is currently licensed against periodontal disease; however, several efforts are underway to develop a vaccine [ 20 ]. Herein, reverse vaccinology was integrated with subtractive proteomics to prioritize potential vaccine candidates in the proteome of oral pathogens, especially P. gingivalis followed by epitopes mapping using immunoinformatic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs this has been seen for house dust mite allergens and skin epithelial cells [ 10 , 11 ], but the effect of allergens on canine buccal epithelial cells has not yet been studied. Apart from antigen-specific tolerance, also pathogen-specific protective mucosal immune responses can be generated by vaccines that are administered onto the oral mucosa [ 12 14 ]. Recently, an oral Bordetella bronchiseptica vaccine has been developed for dogs which involves dripping the vaccine antigens onto the oral epithelium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%